LITERATURE REVIEW: PREVENTION OF ANTERIOR LIGAMENT INJURY WITH PLYOMETRIC EXERCISE IN PRE-ELDERLY - Endah Sri Wulandari; Linda Pramusinta; Ismonah (STIKES Telogorejo Semarang, 2022)
Background : The aging process is associated with a progressive decline in neuromuscular function, increased risk of injury and fractures, impaired functional performance, and loss of independence. Plyometric training can reduce or even improve the ability of the anterior ligament mass. However, little research has been done on the effects of plyometric training on the elderly.Research objective : To prevent anterior ligament injuries in pre-elderly.Methodology : The method used is a literature review of several articles on plyometric exercises to prevent anterior ligament injuries.Results : Plyometric training can have a significant effect on preventing anterior ligament injuries in pre-elderly.Conclusion : Giving exercise therapy can increase daily physical activity in pre-elderly.